EVALUATION OF LEARNING PROGRAMS WITH THE CIPP MODEL IN COLLEGE A THEORETICAL REVIEW - Endang Suparman; Karja Sangadji (Peneliti.net, 2020)
Evaluation as a process of determining at what level educational goals are actually realized. Program evaluation is an